1993
DOI: 10.1002/(sici)1097-4571(199306)44:5<245::aid-asi1>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Children's information retrieval behavior: A case analysis of an OPAC

Abstract: This article reports research that explored children's information retrieval behavior using an online public access catalog (OPAC) in an elementary school library. The study considers the impact of a variety of factors including user characteristics, the school setting, interface usability, and information access features on children's information retrieval success and breakdown. The study reports the overall patterns of children's behavior that influence success and breakdown in information retrieval as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
84
0
7

Year Published

1995
1995
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(92 citation statements)
references
References 18 publications
1
84
0
7
Order By: Relevance
“…Typing also compounds the challenge of spelling words correctly. Solomon found spelling and typing difficulties to be the most common reason for search failure with children aged 7-11 [20]. In addition, children tended to make more spelling errors when the query was more complex.…”
Section: Typing and Spellingmentioning
confidence: 99%
“…Typing also compounds the challenge of spelling words correctly. Solomon found spelling and typing difficulties to be the most common reason for search failure with children aged 7-11 [20]. In addition, children tended to make more spelling errors when the query was more complex.…”
Section: Typing and Spellingmentioning
confidence: 99%
“…Developing new technologies appropriate for children can be challenging, since young people can have difficulty reading, typing, spelling, and are continually changing in their interests and abilities [6,9,14,18,20]. While there is an emerging and significant research field devoted to digital libraries and information retrieval, we have found that the vast majority of content and interfaces are targeted at adults or older students.…”
Section: Children's Digital Librariesmentioning
confidence: 99%
“…People',s labels and those of current classification schemes often don't match. This leads at times to frustration and the inability of such systems to well serve the functions for which they were designed (Solomon, 1993). Consider too the scope and scale of the Internet and the likelihood that there will be thousands of hits in response to a query.…”
Section: Stability and Changementioning
confidence: 99%